Assessment of rhIL-11 by Validated SE-LC Method and its Correlation with RP-LC and CZE Methods - Souto, Ricardo B.; Perobelli, Rafaela Ferreira; Xavier, Bruna; Stamm Maldaner, Fernanda Pavani; da Silva, Francielle Santos; Remuzzi, Gabriel Lunardi; Dalmora, Sergio Luiz (Current Pharmaceutical Analysis, 2018)
Background: Recombinant human interleukin-11 (rhIL-11) is a cytokine produced by recombinant DNA technology and used clinically to treat chemotherapy-induced thrombocytopenia. A Size Exclusion Liquid Chromatography (SE-LC) method was validated to assess the content/potency of the rhIL-11. Methods: A BioSep-SEC-S2000 column (300 mm 7.8 mm i.d.) maintained at 30°C was used. The mobile phase was composed of 0.02 M 2-(N-morpholino)ethanesulfonic acid and 0.5 M sodium chloride buffer, pH 6.0, run isocratically at a flow rate of 0.9 mL min-1, with detection by Photodiode Array (PDA) detector set at 220 nm. Results: Chromatographic separation was obtained with a retention time of 8.12 min, and the stabilityindicating capability, and specificity was demonstrated. The method was linear over the concentration range of 1.0–200 μg mL-1 (r2= 0.9996) and the Detection Limit (DL) and Quantitation Limit (QL) were 0.23 μg mL-1 and 1.0 μg mL-1, respectively. The accuracy was 99.81% with bias lower than 0.43%. Moreover, method validation showed acceptable results for precision and robustness. Conclusion: The method was applied to the assessment of rhIL-11 and Higher Molecular Weight forms (HMW) in biopharmaceutical formulations, and the results of content/potencies were correlated to those of a validated Reversed-Phase Liquid Chromatography (RP-LC) and a Capillary Zone Electrophoresis (CZE) methods, showing non-significant differences (p> 0.05). The proposed method and the correlation studies contribute to monitor stability, improve the quality control and ensure the batch-to-batch consistency of the biotherapeutics.
Keywords: correlation